Patient Advocates in Research: New Possibilities, New Problems - Rebecca Dresser (Washington University Journal of Law & Policy, 2003)
The focus of this Essay, patient advocacy in research, has a somewhat lower profile. This topic is particularly important, however, because it raises issues that touch on many of the topics that keep bioethics in the public eye. The first part of this Essay supplies background information on advocacy activities. The second part describes five themes in research advocacy. In the third part, I propose three ethical principles to guide research advocacy. I close by discussing three future challenges for patient advocates.
Keywords: Bioethics; Medicine -- Research; Patient advocacy